Evaluation of the coefficient of hardening of AISI 1045 steel deformed by roller (Nexo Revista Científica, 2012)
The objective of the work is to determine the behavior of the hardening coefficient n by the equation of Hollomon, in cylindrical samples of steel AISI 1045, those which, after the deformed, were subjected to traction rehearsals. He used an experiment design where are kept in mind the revolution number (n) with 27, 54 and 110 rev/min, it compression forces (P) of 500, 1 500 and 2 500 N and feed (S) of 0.075; 0.125 and 0.25 mm/rev. Finally, applying the regression method a hardening coefficient was obtained, which approaches to the linearity when restrict the calculation to high ranges of deformation. This hardening coefficient is applied in the equation of Hollomon for determine the new value of flow tension and to apply in the calculation of the minimum work to carry out in a cold process of deformation using simple roller.Keywords: Plastic deformation; stress; deformation; hardening.DOI: http://dx.doi.org/10.5377/nexo.v24i2.658